Sheila Reed and John Reed interviewed by Margaret Neale and Jan Adams in the Christmas Island life story oral history project - Reed, Sheila; Reed, John.; Neale, Margo; Adams, Jan. (1986)
Sheila Reed and John Reed were Christmas Island residents at the time of this recording.
Part of a collection related to the social history of Christmas Island and recorded by Marg Neale and Jan Adams.
Digital master available
Published in: We were the Christmas Islanders: reminiscences and the recollections of the people of an isolated island, the Australian Territory of Christmas Island, Indian Ocean / Margaret Neale assisted by Jan Adams. Chapman, A.C.T.: B. Neale, 1988.
Keywords: Christmas Island (Indian Ocean) -- History; Christmas Island (Indian Ocean) -- Social conditions; Christmas Island (Indian Ocean) -- Social life and customs